Studi Eksperimental Performansi Sistem Pendinginan Maisotsenko Udara Counter Flow Dengan Variasi Laju Aliran Massa Udara Primer - Rohman, Fikri Nur; Wijaksana, Hendra; Surya, I Gede Teddy Prananda (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstract The increasing use of non-renewable energy causes increasing greenhouse gas emissions, so that this can have a negative impact on the environment. One of the uses of non-renewable energy that needs to be reduced is the cooling sector. Environmentally friendly energy in the cooling sector is the use of evaporative cooling, one of which is M-IEC which is included in indirect evaporative cooling and is included in the development of the evaporative cooling type, because it combines the direct evaporative cooling process and indirect evaporative cooling. In this study, the Maisotsenko-Indirect Evaporative Cooling cooling system was carried out with a counter flow air pattern by varying the primary air mass flow rate of 0.055296 kg / s, 0.041472 kg / s and 0.027648 kg / s. The distribution of the primary air mass flow rate will greatly affect the inlet air temperature and outlet air temperature, the highest ?TDB is obtained at a primary air mass flow rate of 0.027648 kg/s, the highest wet bulb effectiveness (?wb) and dew point effectiveness (?dp) occur at a primary air mass flow rate of 0.027648 kg/s due to the factor that the lower the air mass flow rate, followed by the low dry bulb temperature will produce higher effectiveness. The highest cooling capacity (Qs) occurs at a primary air mass flow rate of 0.05296 kg/s because the maisotsenko cooling system depends on the high dry bulb inlet temperature and its air mass flow rate so that it will produce a greater cooling capacity. The highest energy efficiency ratio (EER) occurs at a primary air mass flow rate of 0.05296 kg/s, the amount of EER is highly dependent on the cooling capacity produced, where the cooling capacity will also increase with the increase in the primary air mass flow rate. Keywords: Evaporative cooling, M-IEC, variation of air mass flow rate, air temperature distribution, temperature drop difference, wet bulb effectiveness, dew point effectiveness, cooling capacity, cooling rate and energy efficiency ratio.